Collected data on bending, vibration, and push-out tests of shallow steel-timber composite beams—Nordic systemZenodo - Aku Aspila; Markku Heinisuo; Virpi Leivo; Mikko Malaska; Kristo Mela; Sami Pajunen; Mika Vuorela (Data in Brief)
In a slim-floor structural system, beams and slabs are placed at the same level, reducing the overall floor height and material usage in vertical structures, thereby improving economic efficiency. The use of slim-floor structures is common practice in Finnish construction where these structures are typically constructed using hollow-concrete slabs and welded steel box beams. However, in Finland, only a few buildings utilise cross-laminated timber (CLT) slabs in slim-floor structures, and none have incorporated the composite action between CLT and steel beams. This paper presents the laboratory test results of combining CLT slabs and asymmetric welded box beams (WQ-beams) to further assess their potential in optimising structural performance. The structural behaviour of the test construction was evaluated for serviceability and ultimate limit states. The testing involved six full-scale specimens to observe structural responses by measuring total jack forces, deflections, strains, and slip between timber and steel. Vibration tests were conducted on four specimens, capturing deflection and acceleration during heel-drop and walking tests. Additionally, push-out tests were performed to determine connection properties of the wood screws by measuring jack force and displacements. The same skilled faculty team meticulously carried out all tests in the Structural Behaviour Laboratory at Tampere University in Finland. The comprehensive datasets are presented in Excel sheets along with illustrative graphs. Furthermore, the report contains images taken during and after the tests. The provided dataset can serve construction companies, product developers, and researchers aiming to deepen their understanding of the structural behaviour of steel-timber slim-floor composite structures. Additionally, it can be utilised as a reliable reference to validate finite element models (FEM) and analytical calculation models, and to aid in the development of design guides or standards.